Identifying and ranking the components of entrepreneurship implementation in public universities - Hakkak, Mohammed (2024)
The present study was to identify the implementation components of entrepreneurial universities. The components were identified and ranked into five dimensions which are management, services, relationship with society, infrastructure, and output. To determine the weight of the components, type-2 fuzzy analytic hierarchy process (AHP) and decision-making trial and evaluation laboratory (DEMATEL) methods was used. The results indicated that relationship with society was an effective dimension, due to its positive D-R value. Management and infrastructure were considered as the affected ones because of their negative D-R values. Since universities and colleges are facing great paradoxes such as low financial resources, high volume of academic activities, speed and flexibility in development of new fields of study, they are required to find an entrepreneurial answer to the growing imbalance in the relationships between universities and their surrounding environments in order to gain better chances to control their destiny.